2015
DOI: 10.1073/pnas.1503613112
|View full text |Cite
|
Sign up to set email alerts
|

Even with nonnative interactions, the updated folding transition states of the homologs Proteins G & L are extensive and similar

Abstract: Experimental and computational folding studies of Proteins L & G and NuG2 typically find that sequence differences determine which of the two hairpins is formed in the transition state ensemble (TSE). However, our recent work on Protein L finds that its TSE contains both hairpins, compelling a reassessment of the influence of sequence on the folding behavior of the other two homologs. We characterize the TSEs for Protein G and NuG2b, a triple mutant of NuG2, using ψ analysis, a method for identifying conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 68 publications
6
32
0
Order By: Relevance
“…The present study produces a picture of an extensive TSE, as observed for six other proteins studied using ψ (36,37,41,(48)(49)(50). Their TSEs adopt a high fraction of the native topology, defined using the relative contact order (RCO) parameter, RCO TSE ∼ 0.7·RCO N .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The present study produces a picture of an extensive TSE, as observed for six other proteins studied using ψ (36,37,41,(48)(49)(50). Their TSEs adopt a high fraction of the native topology, defined using the relative contact order (RCO) parameter, RCO TSE ∼ 0.7·RCO N .…”
Section: Discussionmentioning
confidence: 69%
“…4 and Table S3). The addition of zinc or nickel ions, which coordinate the pair of histidines, alters the protein's stability and activation free energy for folding (ΔΔG eq and ΔΔG f , respectively) due to differences in binding constants K DSE , K N , and K TSE (35)(36)(37). The ion-induced changes in ΔΔG eq and ΔΔG f are used to define the ψ value, a parameter analogous to the mutational ϕ value, with ψ being the instantaneous change in ΔΔG f relative to ΔΔG eq ,…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has already shown that a single mutation may greatly affect the structure, stability or function of a protein [ 3 , 4 ], but some proteins significantly differ in sequence are found to share very similar structures and functions [ 1 , 2 ]. To unravel this mystery, folding of homologous proteins has been compared [ 5 , 6 ] with peripheral subunit binding domains [ 7 , 8 ], homologs protein G & L [ 9 ], spectrin domain R15, R16 and R17 [ 1 ] and RNase family [ 10 ]. It is noticed that some homologues share very similar folding mechanism [ 5 , 9 ], while some others significantly differ thermodynamically and kinetically [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to an off-pathway kinetic trap. Although previous work has also identified nonnative states involving these hairpins docked in an anti-parallel orientation [38], our work provides a quantitative estimate of the effect of these nonnative contacts on folding kinetics. Namely, our finding that a significant fraction of the population adopts long-lived states in which the hairpins misalign in an antiparallel fashion ( Fig.…”
Section: Use Of Dbfold To Generate Experimentally-testable Predictionsmentioning
confidence: 85%
“…As a proof of principle, we now apply our method on Streptocaccal Protein G, a model protein whose folding has been extensively studied using both computational and experimental methods [20,[31][32][33][34][35][36][37][38]. We begin by running equilibrium simulations with replica exchange and umbrella sampling using native contacts as the reaction coordinate along which we bias [39] (See Materials and methods).…”
Section: Computing Equilibrium Folding Properties For Protein Gmentioning
confidence: 99%